¿Is it more effective learning a foreign language in a CLIL context? Research results in Spain (Journal of Parents and Teachers, 2013)
The article analyses the implementation of Content and Language Integrated Learning (CLIL) programs in Spain designed to improve students' communicative competence in the foreign language. It shows an overview of the results of research carried out in Spain across different educational levels (primary, secondary and tertiary), distinguishing between those that analyse overall language competence in English and those that examine specific language competencies (lexical, phonetic, morphosyntactic, etc.). The authors conclude that CLIL results in better general language proficiency, but that gains in specific language areas are not so conclusive. In addition, they note that the research carried out at different educational levels is still extremely fragmentary and heterogeneous. In the light of this evidence, the authors suggest both a greater focus on form in the CLIL classroom and a more integrated approach to CLIL research across educational levels.
Keywords: CLIL; general competence; formal aspects; focus-on-form